Academic English Needs and Practices of Faculty and Students at a Public University in Medellín, Colombia - Correa, Doris; Montoya, Juan Carlos (Íkala, Revista de Lenguaje y Cultura, 2025)
With current internationalization trends, universities have taken a series of measure to increase faculty and students’ academic English. Nonetheless, little has been done to discover what faculty and students’ English needs and practices really are currently, how their needs relate to their practices, or how needs and practices differ by population. To fill this gap, researchers from a public university in Medellín sent a questionnaire to faculty and students via email inquiring about this. The results indicate that: (a) although there are differences in terms of age, gender, ethnicity, and hiring status, both groups need support with academic English skills such as writing and publishing academic texts, conference and grant proposals, and research reports; (b) there is a mismatch between what both students and faculty need and what they practice in English; and (c) students need the development of all listed skills much more than faculty. These results suggest the need for universities to: (a) consider demographic variables when designing programs for these populations, (b) develop programs that prioritize what is needed by both groups over what is practiced by them, and (c) focus on students, as they are the ones more highly in need of all skills.